Stress and coping strategies in the presence of breast cancer-Preview Note - Alves, Pricilla Cândido; Fernandes, Ana Fátima Carvalho (Online Brazilian Journal of Nursing, 2010)
Descriptive-exploratory study with a quantitative approach whose aim is to verify the occurrence of stress and the use of coping strategies in the daily of women with breast cancer. It will be realized in the outpatient mastology of School Maternity Assis Chateaubriand, located in Ceará with a sample of 145 women. The data collection will happen from June to August 2010 and it will be used like instruments a interview guide about the study’s women characteristics and the disease’s history, the Stress Symptoms Inventory for Adults Lipp (ISSL) and the Ways of Coping Scale (WCS). The verification of relation statistics among the variables studied will be made with the program Statistical Package for the Social Sciences (SPSS) version 17.0.